RANCANG BANGUN MONITORING KEBERADAAN ORANG DENGAN MEMANFAATKAN LAYANAN SMS DAN INTERNET SEBAGAI MEDIA TRANSFER DATA - Nurhadi, Nurhadi; Sutanto, Teguh; Taufik, Vicky M. (Jurnal JSIKA, 2013)
Parents activities reduced their attention to children. Sometimes parents do not know their children’s activity. Even they did not know where their children. So it is not uncommon today´s children often go to places that are not fitting. Even worse was the kidnapping of children.